COMPARISON OF FOUR DIAGNOSTIC PHENOTYPIC METHODS FOR DETECTION OF METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS (MRSA) - MUNDHADA G. SAPANA; INGOLE V.KISHOR; BHISE P.MAYURI; POWAR M.RAJARAM (International Journal of Pharma and Bio Sciences, 2016)
Rapid and accurate detection of Methicillin-resistant Staphylococcus aureus (MRSA) is an important role of microbiology laboratories. The present study was aimed to compare various phenotypic methods for detection of MRSA.92Staphylococcus aureus isolates obtained from various samples were tested for methicillin resistance by cefoxitin disc diffusion, oxacillin disc diffusion and oxacillin screen agar considering E test MIC(oxacillin) as gold standard. Antibiotic susceptibility testing was done for MRSA.32 (34.78%) isolate were identified as MRSA by E test MIC. Cefoxitin disc diffusion showed 100% sensitivity and 98.30% specificity while oxacillin disc diffusion and oxacillin screen agar showed 100% sensitivity and 86.66% and 90% specificity respectively. Among MRSA high degree of resistance was seen for routinely use antibiotics but 100% sensitivity to Linezolid and Vancomycin. It is conclude that cefoxitin disc diffusion test is reliable substitute for detection of MRSA in laboratory where MIC detection and molecular methods are not accessible.